Science,Technology & Society - Owen-Smith, Jason (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This Ph.D. level seminar offers students a broad overview of sociological, economic, and interdisciplinary approaches to the study of science and technology with a particular focus on reciprocal relationships across socio-cultural, economic, and technical systems. The traditional sociological approaches to knowledge and science postulates a strong boundary between society and scientific practice. Similarly, economic studies of technological change and innovation draw (implicitly or explicitly) a distinction between science and technology. Current research in the interdisciplinary field of Science and Technology Studies problematizes these distinctions and, in so doing, offers the opportunity for a theoretical rapprochement between sociological and economic approaches to science and technology.